2022
DOI: 10.1186/s13099-022-00487-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective investigation into the association between the gut microbiome composition and cognitive performance among healthy young adults

Abstract: Background There is emerging evidence that the gut microbiome composition is associated with several human health outcomes, which include cognitive performance. However, only a few prospective epidemiological studies exist and none among young adults. Here we address the gap in the literature by investigating whether the gut microbiome composition is prospectively linked to fluid intelligence among healthy young adults. Methods Forty individuals (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Overall, research suggests that dysbiosis of the intestinal microbiota and increased intestinal permeability (commonly, but not exclusively, due to dysbiosis) can affect brain function, mental health, and behavior [3,16,31,35,[57][58][59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, research suggests that dysbiosis of the intestinal microbiota and increased intestinal permeability (commonly, but not exclusively, due to dysbiosis) can affect brain function, mental health, and behavior [3,16,31,35,[57][58][59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…However, higher fractions of Bacteroides have also been linked to higher cognitive functioning, as reported by other teams (Carlson et al, 2018;Tamana et al, 2021). Besides, while Oluwagbemigun et al (2022) have observed that Ruminococcaceae-and Coriobacteriaceaedominant communities are associated with higher intelligence scores, some have reported that (i) Firmicutes-dominant and Bacteroidetesdominant clusters (Tamana et al, 2021) are positively associated with higher cognitive functioning. In analyzing the age of the participants in the preceding studies (adults for some studies and infants for the other studies), one may legitimately believe that the relationship between gut microbiota composition and cognition and/or overall intelligence depends on age.…”
Section: Perspectivesmentioning
confidence: 78%
“…Further investigations are therefore required in this regard. It is, however, important to note that Oluwagbemigun et al (2022) have observed that Akkermansia and other bacteria (Ruminiclostridium 5, Ruminococcaceae UCG-010, Coriobacteriaceae, Slackia, the Eubacterium hallii group, Peptoclostridium, Lactococcus, Erysipelotrichaceae incertae sedis, Eubacterium nodatum group, Prevotellaceae, Robiginitalea, Pseudomonas, and the Bacteroidales S24-7 group) are associated with fluid intelligence, which in turn, according to van Aken et al (2016), correlates with cognitive performance. In the absence of a definitive list of bacteria influencing human intelligence, the list provided by Oluwagbemigun et al (2022) is informative, and represent an important platform from which researchers may launch further investigations, particularly in an HIV infection-related context.…”
Section: Geotrichum Capitatummentioning
confidence: 99%
See 1 more Smart Citation
“…More accurate calculations put the relative ratio at slightly over 1 microbe to every human cell [ 8 ]. Over a thousand strains of bacteria have been identified in the gut microbiota [ 9 , 10 , 11 ]. Many of these strains remain unculturable and have been identified by sequencing.…”
Section: Architecture Of Gut Microbiotamentioning
confidence: 99%